PeriScope: An Effective Probing and Fuzzing Framework for the Hardware-OS Boundary - Dokyung Song; Felicitas Hetzelt; Dipanjan Das; Chad Spensky; Yeoul Na; Stijn Volckaert; Giovanni Vigna; Christopher Kruegel; Jean‐Pierre Seifert; Michael Franz (2019)
The OS kernel is an attractive target for remote attackers.If compromised, the kernel gives adversaries full system access, including the ability to install rootkits, extract sensitive information, and perform other malicious actions, all while evading detection.Most of the kernel's attack surface is situated along the system call boundary.Ongoing kernel protection efforts have focused primarily on securing this boundary; several capable analysis and fuzzing frameworks have been developed for this purpose.However, there are additional paths to kernel compromise that do not involve system calls, as demonstrated by several recent exploits.For example, by compromising the firmware of a peripheral device such as a Wi-Fi chipset and subsequently sending malicious inputs from the Wi-Fi chipset to the Wi-Fi driver, adversaries have been able to gain control over the kernel without invoking a single system call.Unfortunately, there are currently no practical probing and fuzzing frameworks that can help developers find and fix such vulnerabilities occurring along the hardware-OS boundary.We present PERISCOPE, a Linux kernel based probing framework that enables fine-grained analysis of device-driver interactions.PERISCOPE hooks into the kernel's page fault handling mechanism to either passively monitor and log traffic between device drivers and their corresponding hardware, or mutate the data stream on-the-fly using a fuzzing component, PERIFUZZ, thus mimicking an active adversarial attack.PER-IFUZZ accurately models the capabilities of an attacker on peripheral devices, to expose different classes of bugs including, but not limited to, memory corruption bugs and double-fetch bugs.To demonstrate the risk that peripheral devices pose, as well as the value of our framework, we have evaluated PERIFUZZ on the Wi-Fi drivers of two popular chipset vendors, where we discovered 15 unique vulnerabilities, 9 of which were previously unknown.